Grafting of 2-Hydroxypropyl Methacrylate onto Poly(ethylene terephthalate) Fibers and Dye Ability - Azizinezhad, Fariborz (Asian Journal of Chemistry, 2010)
In this study, dye ability of the poly(ethylene terephthalate) fibers after grafting with 2-hydroxypropyl methacrylate is reported using Disperse Red S-BFW as disperse dye. Results of the dye ability showed that by increasing of the percentage of grafted fibers, their dye ability increases to 21.21 %-grafted product and then decreases. The effect of 0.5 % emulsifier (anionic, cationic and nonionic) on fibers dye ability was investigated. While at the presence of cetyltrimethyl ammonium bromide no dye ability could be observed, in dyeing of uncopolymerized fibers, the effect of hexadecyl poly[oxyethylene(30)] alcohol (OC-30) was more than sodium lauryl sulphate and cetyltrimethyl ammonium bromide. But in graft product with the increase of the graft product, sodium lauryl sulphate, cetyltrimethyl ammonium bromide and OC-30 showed more dye ability effect on the fibers, respectively. On the other hand, with the use mixture initiators including benzoyl peroxide (Bz2O2), 4-4'-azobis(4-cyanovaleric acid) (ACV) an intensifying effect on the graft product was observed and the copolymerization time at the presence of (Bz2O2/ACV = 1/3) decreased. The characterization of graft fibers with thermogravimetric analysis, scanning electron microscopy and Fourier transform infrared methods have been investigated.